Diseño de máquina de limpieza mecánica para la inspección de áreas exteriores críticas de tuberías de perforación, con diámetros entre 3” y 7” (inch), para la empresa South American Inspection Services Colombia S.A.S. (2021)
The main objective of this document is to design a mechanical cleaning machine for the inspection of critical external areas of drill pipes, with diameters between 3 ”and 7” (inch), for the company South American Inspection Services Colombia S.A.S., which at the date does not have any official or unofficial design for the design of said machine. This company is dedicated to providing exploration and / or production tools and equipment services in the hydrocarbon sector. Therefore, this document deals with showing in detail the design of the drill pipe inspection mechanical cleaning machine. Initially, the characterization of the company is recounted, in order to account for the problems that arose in its context. Then, the designs, mathematical analyzes, among others, are presented. Finally, the final design for the mechanical cleaning machine that meets the needs of the company is revealed.